Correction: Liu et al. Two-Stage Multimodal Method for Predicting Intramuscular Fat in Pigs. Agriculture 2024, 14, 1843 - Wenzheng Liu; Tonghai Liu; Jianxun Zhang; Fanzhen Wang (Agriculture)
In the published article [...]